EFFECT OF THE COMBINATION OF CHITOSAN AND ZEOLIE/CU2+ ON THE PRESERVATION OF SUGAR APPLE (Annona squamosa L.) - Pham Quang Thang; Le Si Ngoc; Pham Thi Ha Van; Nguyen Chau Anh; Vu Thi Thu Thao (HUIT Journal of Science, 2024)
Sugar apples were harvested and stored immediately when they reached harvesting maturity. Sugar apples were dipped in 2% chitosan and were then air-dried. After that, they were put into the carton and placed zeolite/Cu2 in a barrel and the fruit was stored at (10 ± 1)ºC in cold storage, humidity 80 - 85%. The results revealed that the preservation of the sugar apples with 5 packets (5 g/packets) of zeolite/Cu2 /barrel after coating them with 2% chitosan was better. Sensory and nutritional qualities of the fruits were maintained through a storage period of 12 days at 10 ºC.